HAK ASUH ANAK PASCA PERCERAIAN (Studi Pada Kantor Pengadilan Agama Kota Makassar) - Agus, Andi Aco; Hariyani, Hariyani (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2018)
This study aims to determine: 1) Constraints in handling divorce cases in the Religious Makassar, 2) Impact of divorce on children after divorce in the Religious Makassar. This study used a qualitative approach. This study took place in the Religious Makassar. The types and sources of data used in this research is the primary data sources (informants) and secondary data sources. Data collection techniques in this research is interview and documentation. Data analysis technique used is descriptive qualitative data analysis techniques. Menunujukan research results that: 1) Constraints in handling divorce cases is the lack of mediation success rate. Because most of those litigants experiencing domestic problems which culminated thus more mediation fails, in addition to economic factors, infidelity, including the crisis akhalak very influential in the holding of the mediation process so that both sides were reluctant to get back together again. So that the mediation success rate is very small presentation. 2) The impact of divorce on children that have an impact on children's education. In addition, children also lose a sense of security and affection from parents that affect the physical and psychological development of children and ultimately have an impact on academic achievement.